Peningkatan Kapasitas Kelompok Wanita Tani Melalui Penyuluhan Teknik Pemangkasan Kopi Robusta - Salma Ghaziyah Adhwa; Aidil Azhar; Edi Wiraguna (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2025)
Robusta coffee (Coffea canephora) is one of Indonesia’s important agricultural commodities with strong economic potential. However, optimizing its productivity depends heavily on proper cultivation practices, particularly pruning, which significantly affects plant health and fruit yield. This study focused on the Women's Farmer Group (Kelompok Wanita Tani/KWT) in PTPN 1 Regional V Kebun Bangelan, East Java, which faced challenges due to limited skills and knowledge in coffee pruning. A community-based agricultural extension program was implemented to enhance their technical capabilities and ensure compliance with standard operating procedures (SOP) for effective pruning. The objectives were to identify key issues in pruning practices, deliver targeted training, and evaluate the outcomes. Using a mixed-methods approach—comprising participatory observation, structured interviews, focus group discussions (FGD), and a pre-test/post-test comparison—the study assessed knowledge gains and training impact. A Likert-scale survey further measured participant satisfaction. Findings revealed four main issues: low SOP adherence, lack of training, poor tool maintenance, and plant morphological constraints. Post-intervention, participant knowledge rose from 49% to 97%, a 48% improvement. Additionally, 71.88% of respondents rated the training positively. This indicates that structured, practical training significantly improved pruning skills, contributing to better agricultural practices and productivity in smallholder communities.